Pengembangan Kewirausahaan Minuman Kreatif melalui Pelatihan Coffee Mixology dan Strategi Pemasaran Digital untuk Mendukung Ekonomi Kreatif di Kawasan Wisata Takapala Malino - Resky Faradibah Suhab; Andi Hasbi; Muh. Arif; Nurlaila Dahlan; Hilda Apriani; Sabran Laori D (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The development of the creative economy has become an important strategy for strengthening tourism destinations and improving local community welfare. However, many tourism communities still face challenges in developing innovative products and utilizing digital marketing to enhance competitiveness. This community service program aimed to improve entrepreneurial capacity through coffee mixology training and digital marketing strategies in the Takapala Malino Tourism Area, Gowa Regency, Indonesia. The program was implemented using participatory methods consisting of socialization, demonstration, hands on practice, and mentoring activities involving 30 participants, including local tourism stakeholders, micro and small business owners. Participants included local tourism actors, micro and small business owners, youth communities, and residents around the tourist destination. The training introduced participants to creative beverage concepts, coffee mixology techniques, product innovation, beverage presentation aesthetics, branding, and digital marketing practices. The results demonstrated increased participant knowledge and skills in developing coffee based creative beverages such as Strawberry Americano, Cold Brew, Rainbow Fizz Strawberry, Rainbow Fizz Orange, and Pandan Milk Coffee. Participants also gained a better understanding of social media utilization, content creation, and digital promotion strategies for tourism-related products. The program successfully enhanced entrepreneurial motivation and encouraged the creation of value added beverage products that support the creative economy and tourism attractiveness of Takapala Malino. Continuous mentoring and business development programs are recommended to ensure long term sustainability and economic impact.